Supervisi Akademik Kepala Madrasah - Ari Prayoga; Supiana (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2020)
The madrasah headmaster did not take the initiative to approach the teaching staff to find out the constraints experienced while teaching and was not yet too intensive in implementing the clinical approach to the teaching staff. This study aims to uncover the processes of academic supervision including; planning, implementing and follow up supervision results at Madrasah Aliyah Darussalam Sumedang. The research method used is qualitative. Data collection techniques using interviews, observation and documentation study. The results showed that; First, the implementation of academic supervision is carried out by compiling an academic supervision program and creating a supervision team that is given the task of making academic supervision goals and making an academic supervision schedule. Second, the implementation of academic supervision using approaches and supervision techniques; conduct class visits, observe the activities of teaching staff in teaching, observe the mastery of teaching staff towards teaching materials, conduct group discussions. Third, follow up on the results of academic supervision of teaching staff by discussing learning methods, the use and assessment techniques, the use of instructional media and the use of time in learning.